A classroom that children wish for: redefining the classroom space while honouring primary school students’ voices - Dettori, Filippo (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2017)
This contribution is the result of a study conducted on classroom space. It involved a group of primary school students during a learning laboratory organised by researchers from the Faculty of Education and the Faculty of Architecture from the University of Sassari. During the laboratory, children were given the opportunity to express their thoughts on how a classroom space should be so as to make learning easier for all students. Drawing from the students’ experience, the participants developed projects of classroom spaces and explained to the researchers the reasons why they had positioned the furniture in that specific location. What clearly emerged from their projects, as well as from the students’ statements, was the need for a classroom space that was more suitable and that allowed a more cooperative and lab-style learning. What emerged from the children’s classroom organisations was that students clearly asked for a less transmissive type of school and a space where students can become more competent through a concrete way of doing and a constant direct contact with their teachers and classmates.